"Alexa, define empowerment": voice assistants at home, appropriation and technoperformances. Issue 2 (10th May 2021) - Kudina, Olya; Coeckelbergh, Mark
Abstract : Purpose: This paper aims to show how the production of meaning is a matter of people interacting with technologies, throughout their appropriation and in co-performances. The researchers rely on the case of household-based voice assistants that endorse speaking as a primary mode of interaction with technologies. By analyzing the ethical significance of voice assistants as co-producers of moral meaning intervening in the material and socio-cultural space of the home, the paper invites their informed and critical use as a form of (re-)empowerment while acknowledging their productive role in human values. Design/methodology/approach: This paper presents an empirically informed philosophical analysis. Using the conceptual frameworks of technological appropriation and human–technological performances, while drawing on the interviews with voice assistants' users and literature studies, this paper unravels the meaning-making processes in relation to these technologies in the household use. It additionally draws on a Wittgensteinian perspective to attend to the productive role of language and link to wider cultural meanings. Findings: By combining two approaches, appropriation and technoperformances, and analyzing the themes of privacy, power and knowledge, the paper shows how voice assistants help to shape a specific moral subject: embodied in space and made as it performatively responds to the device and makes sense of it together with others. Originality/value: The researchers show how through making sense of technologies in appropriation and performatively responding to them, people can change and intervene in the power structures that technologies suggest.